Solve -4*x + 2*w + 13 = -9, 2*w = -6 for x.

4

Solve 0 = -i + 22*u - 18*u + 1, 0 = -i - 2*u - 5 for i.

-3

Solve -3*u + 5*m = 18, u + m + 10 = 4*m for u.

-1

Solve 2*p - 3*l = 1, 41*p = 46*p + l + 6 for p.

-1

Solve 3*z - 1 = 5*u + 9, -u - 5 = 0 for z.

-5

Solve 13 = -i + 4*y, 0 = -6*i + 10*i - 2*y - 4 for i.

3

Solve 0 = -4*g - 20, 0*g = -5*a + 5*g + 50 for a.

5

Solve 0 = -5*x - 2*t + 30, 0 = -x + 2*t + 5 - 11 for x.

4

Solve 4*k - 68 = -5*d - 63, 2*d - 5 = -k for d.

5

Solve 4*g + 7 = 5*v, 2*g + 2*v - v + 7 = 0 for g.

-3